Ancaman Konversi Lahan Sawah Terhadap Kecukupan Beras di Kabupaten Musi Rawas - Alamin Yang First; Baba Barus; Boedi Tjahjono (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2023)
Rice production in 2019 decreased by 2.63 million tons or 7.75 percent compared to 2018, exacerbated by the increasingly massive conversion of agricultural land. One of the areas threatened by land conversion is Musi Rawas Regency in South Sumatra Province. This study aims to analyze changes in land use in 2000, 2010, 2020 and paddy fields for rice sufficiency in Musi Rawas Regency. The method used is Cellular Automata-Markov (CA-Markov), analysis of the surplus-deficit food balance, and paddy fields overlaying the spatial plan. Based on the results of the analysis, there was a change in land use in Musi Rawas Regency between 2000 to 2020, an increase in the area of plantation land by 128,867.74 ha. This increase is largely the result of conversion of paddy fields. The results of the calculation of the predicted demand for rice in 2030 show that in total there will be a rice deficit of -16,511 tons. It is predicted that there will be a rice deficit due to the decrease in the area of paddy fields which is affected by changes in land use from paddy fields to non-paddy fields. The suitability of existing paddy fields with the 2010 to 2030 RTRW shows an area of 7,598.73 ha of actual paddy fields in 2020 is suitable, 3,057.27 ha is not suitable. The incompatibility of paddy fields in 2020 with the RTRW can be input into the revision of the RTRW that will be carried out by the Musi Rawas Regency government, especially on the spatial pattern of paddy fields.